An examination of the influence of emotional solidarity on value cocreation with international Muslim travelers - Chua, Bee-Lia; Al-Ansi, Amr; Han, Heesup; Loureiro, Sandra Maria Correia; Guerreiro, Joao (SAGE Publications, 2022)
Given the rising Muslim travel market and the scarcity of research on Muslim inbound market, it is important to elucidate how international Muslim travelers are perceived through the lens of residents in non-Islamic countries. This study provided an insight into how value cocreation is created through emotional solidarity and attitudes in the context of the Muslim travel market. Results of the structural model for American residents were comparatively similar to those of their Korean counterparts, which is indicative of both countries’ acceptance and tolerance of international Muslim travelers. In particular, residents’ openness to experience and the perceived benefit of international Muslim travelers for development of the tourist destination were significant predictors of emotional solidarity. Residents’ emotional solidarity subsequently explained their attitude toward international Muslim travelers. Attitude toward international Muslim travelers would lead to a positive attitude toward Muslim tourism, which in turn, triggered value cocreation behavior with international Muslim travelers.